The Plurality of Fatwa Authority and Its Impact on the Halal Ecosystem in Indonesia - Farid Wajdi (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This article examines the plurality of fatwa authorities in determining product halalness in Indonesia and its implications for the Halal Product Assurance (JPH) ecosystem. Using a comparative juridical-empirical approach, the study identifies the sources of plurality (interactions between the Indonesian Ulema Council (MUI), the Halal Product Fatwa Committee (BPJPH), and implementing regulations), analyzes its impact on legal certainty and consumer protection, and compares institutional alternatives from Malaysia (the centralized model/JAKIM) and international standard practice (SMIIC). Findings indicate that plurality without a harmonization mechanism creates informational confusion, risks fragmentation of technical standards, and potential erosion of the legitimacy of halal certification; therefore, a formal coordination protocol, an integrated fatwa registry, a fatwa dispute resolution mechanism, and strengthening of technical accreditation are needed.